Disentangling organizational commitment in hospitality industry: The roles of empowerment, enrichment, satisfaction and gender. - Ruiz-Palomo, Daniel; León-Gómez, Ana María; García-Lopera, Francisca (Elsevier, 2020)
This Paper identifies how the motivational strategies of empowerment and enrichment affect on the organizational commitment of hotel staff, and how the job satisfaction mediates in these relationships. We applied a Structural Equations Modeling to a sample of 257 front line hotel employees from Madrid, of which 144 were men and 113 were women. Our results provide evidence about several contributions: first, employees empowerment significantly grows job enrichment and organizational commitment; second, job enrichment increase workers’ satisfaction and commitment; third, job satisfaction enhances organizational commitment; fourth, job enrichment plays a mediating role between empowerment and both satisfaction and organizational commitment; fifth, satisfaction mediates between enrichment and commitment; finally, gender moderates the relationship between enrichment and commitment.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/12572
Keywords: Hoteles y pensiones - Gestión; Hostelería - Personal; PLS-SEM; Empowerment; Enrichment; Satisfaction; Gender; Organizational commitment; Hotel